Encefalitis amebiana granulomatosa por Amebas de Vida Libreen un paciente pediátrico. - Tello Brogiolo, N; Molina , S; Esposto, S; Magistrello , P; Bustamante, J; D´Agustini , M (Revista Argentina de Neurocirugía, 2020)
Introduction: Free-living amoebas (FLA) Naegleria fowleri, Acanthamoeba spp., and Balamuthia mandrillaris, are protist widely distributed in nature. Are opportunistic microorganisms, preferentially affect the central nervous system causing primary amoebic meningoencephalitis or amoebic granulomatous encephalitis (AGE), both with high mortality. Case report: A 10 year-old female patient was admitted with a three-day history of left hemiparesis accompanied with headaches and vomiting. Computed tomography and magnetic resonance were performed, in which an expansive solid cystic mass was observed in the right fronto-parietal region. Complete resection was performed and pharmacological treatment was started, achieving complete restitution of motor function and resolution of AGE after 30 months of follow-up. Discussion: AGE is a desease caused by free-living amoebas. Its clinical presentation is similar to other leptomeningitis or encephalitis of different etiology such as bacterial, viral or by mycobacterial, which cannot know its real incidence. Its pharmacological treatment is complex and its evolution is usually fatal. Conclusion: We report a case of Amoebic Granulomatous Encephalitis in an immunocompetent pediatric patient with good outcome.